Clinical Applications of Electrical Stimulation in Peripheral Nerve Injuries and Entrapment Neuropathies: A Narrative Review - Krupska, Barbara; Wiercioch, Eliza; Zapalska, Magdalena; Włodarczyk, Franciszek; Witczak, Katarzyna; Wieleba, Marcin; Kulig, Lidia; Malec, Julia; Winiarska, Zuzanna; Woźniak, Weronika (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Peripheral nerve injuries and entrapment neuropathies are associated with chronic pain, sensory and motor dysfunction. Although the nervous system has some regenerative capacity, recovery is often incomplete. Electrical stimulation (ES) may enhance axonal regeneration, reinnervation and functional recovery. This study aimed to summarize current evidence on the clinical use of ES in these conditions and to assess its role in everyday practice. Material and methods. A narrative review was performed using PubMed and Google Scholar databases. The search included 22 studies published between 2009 and 2026. Eligible sources included books, original and retrospective studies, reviews, systematic reviews and randomized controlled trials. Case reports, conference abstracts without full text, non-English publications, duplicates, and studies not directly related to the topic were excluded. Results. ES was associated with improved outcomes in several clinical settings. Postoperative ES after carpal tunnel and cubital tunnel decompression improved electrophysiological and functional outcomes. In carpal tunnel syndrome, interferential current therapy provided greater pain relief and better nerve function recovery than splinting or TENS. ES after digital nerve repair improved sensory recovery, while intraoperative ES after neck dissection was associated with better shoulder function and electrophysiological results. However, the evidence is limited by small sample sizes and restricted applicability of some outcome measures in everyday practice. Conclusions. ES appears to be a promising adjunctive treatment in peripheral nerve injuries and entrapment neuropathies, but further studies are needed to standardize protocols and confirm its effectiveness.